Evaluating Training Methods for Facial Image Comparison: The Face Shape Strategy Does Not Work. (February 2014) - Towler, Alice; White, David; Kemp, Richard I
Human performance on unfamiliar face matching is known to be highly error prone. However, in organisations where staff are required to perform this task as part of their daily work, attempts are often made to mitigate risk by providing training. Importantly, the methods used in these training courses have not been subjected to empirical validation. In this study we evaluate a common component of many training programmes which encourages viewers to classify face shape. Our results show very low agreement in face shape classification, both within and between participants, and across repeated presentations of a single image to a single participant. Furthermore, face shape classification training did not improve face matching accuracy, suggesting that the face shape strategy does not facilitate identification.